Solar Energy Driven Adsorption Cycle Cooling Machine Performance with A Collector Area Of 1 M2 And A Collector Inclination of 30o - Daniel C Sibarani (Trigin Publisher, 2021)
Solar Energy is the biggest energy on the earth, solar enegy in Indonesia can be utilized for variety of things. Based on solar radiation data collected from 18 locations in Indonesia, solar radiation for West Indonesia area has reached 4,5 kWh/m2/day with monthly variation about 10%, while East Indonesia area has reached about 5,1 kWh/m2/day with monthly variation about 9%. Therefore, the solar energy can be utilized as the main source of energy for the adsorptionrefrigeration cycle cooling machine to produce cooling effect. In this research, the main component of this machine consist of collector/adsorber, condenser, and evaporator. The surface area of this collector/adsorber is about 1m2and tilted at 30o. The collector filled with about 18,5 kg of activated carbon, meanwhile the evaporator filled with 5 Litres of methanol. The chilled media is 4 litres of water. This experimental lasts for three days, divided by two periods that are desorption process and adsorption process. The result from this experiment was the collector can adsorb solar radiation with daily average about 7.093.769,356 Joule and could decrease the water temperature become 1,85oC at first adsorption cycle, while the ambience temperature about 26,9oC.